Common maternal health problems among Australian-born and migrant women: A prospective cohort study. - Tharanga Navodani; Deirdre Gartland; Stephanie J Brown; Elisha Riggs; Jane Yelland (PLoS ONE, 2019)
BACKGROUND:Migrant women of non-English speaking background make up an increasing proportion of women giving birth in high income countries, such as Australia, Canada and the United Kingdom. The aim of this study was to assess the prevalence of common physical and psychosocial health problems during pregnancy and up to 18 months postpartum among migrant women of non-English speaking background compared to Australian-born women. METHODS:Prospective pregnancy cohort study of 1507 nulliparous women. Women completed self-administered questionnaires or telephone interviews in early and late pregnancy and at 3, 6, 9, 12 and 18 months postpartum. Standardised instruments were used to assess incontinence, depressive symptoms and intimate partner violence. FINDINGS:Migrant women of non-English speaking background (n = 243) and Australian-born mothers (n = 1115) reported a similar pattern of physical health problems during pregnancy and postpartum. The most common physical health problems were: exhaustion, back pain, constipation and urinary incontinence. Around one in six Australian-born women (16.9%) and more than one in four migrant women (22.5%) experienced intimate partner abuse in the first 12 months postpartum. Compared to Australian-born women, migrant women were more likely to report depressive symptoms at 12 and 18 months postpartum. CONCLUSION:Physical and mental health problems are common among women of non-English speaking background and Australian-born women, and frequently persist up to 18 months postpartum. Migrant women experience a higher burden of postpartum depressive symptoms and intimate partner violence, and may face additional challenges accessing appropriate care and support.